RELEASE AND DISCHARGE AGREEMENT IN THE COMPENSATION SETTLEMENT BY AIRLINES COMPANY (A NATIONAL AND INTERNATIONAL LAW PERSPECTIVE) - Nida Wafiqah; Rosmawati Rosmawati (Universitas Syiah Kuala, 2021)
This paper analyses the rules and implementation regarding the Release and Discharge Agreement in the compensation settlement process by airlines company based on national and international law. The results show that this release and discharge agreement is not per Article 186 of the Aviation Law, which regulate that the carrier as a business actor is prohibited from making special agreements or requirements that negate the carrier's responsibility or determine a lower limit than the current compensation limit. According to international law, this release and discharge agreement does not follow Article 26 of the 1999 Montreal Convention, which regulates that airlines companies are not allowed to form contracts that may reduce or eliminate the amount of liability. Hence, obstacles arise in the ccompensation settlements when using Release and Discharge Agreement documents, the method of airline liability, and proving the cause of the accident to exclude the payment of compensation settlements to passengers. It is recommended to improve the rules related to the carrier's responsibility to ensure that passengers could get their rights according to the provisions contained in the legislation and maximize the implementation of international conventions related to aviation that have been ratified into national regulations. Keywords: Compensation, Liability, Release and Discharge Agreement, Airline Company, Passenger.